ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT REPORT LAG PADA PERUSAHAAN SEKTOR KEUANGAN - Anak Agung Putu Gede Bagus Arie Susandya (Jurnal AKSES, 2021)
The survival of the company always survives with the timeliness of financial reports. When financial reporting occurs, it will prevent investors or creditors from making decisions. This study aims to test and obtain empirical evidence regarding the influence of company size, company age, solvency, size of KAP, auditor opinion on financial sector companies listed on the Indonesia Stock Exchange in 2017-2019. The research population is all financial sector companies listed on the Indonesia Stock Exchange in 2017-2019. The sample in this study were 222 obtained based on purposive sampling technique. The analysis technique used is Multiple Linear Regression Analysis. The results showed that company size and KAP size had a negative effect on audit reports, while company age, solvency, and auditor opinion had no effect on audit report lag. Further research can develop this research by adding other variables that theoretically affect the audit report, as well as increasing the research period or changing the sample used